Narrativas da velhice: entrelaces do discurso acerca do luto - Olesiak, Luísa da Rosa (2019)
Old age is permeated by stigma and a paradoxical experience at contemporary times, in the face of a society that on one hand constantly seeks to prolong life to not encounter death, and on the other it strives to distance itself from the reflexes of its presence. Reflexes that overlap by changes that touch the subject means, his body, psyche and relationships, in order to portray inevitable losses in the development process. In this scenario, the contemporary Western society, which values the production and the imperative of happiness, has as characteristic the aversion to the losses and the finitude, being these extinct of the reflections and social guidelines. In this way, images are often constructed about old age, intertwined in the idea that denotes only healthy aspects and joy, removing everything that refers to possible losses of the symbolic and real order, which reverberates in the absence of spaces for the elaboration of the same ones. In addition, this whole process demands to think about the others look directed to the elderly, which still today refers to the idea of fragility and being defenseless, so as not to accept the anxieties and help them in the elaboration of their experiences. In the face of this, the objective of this research is to understand how the elderly subjects mean old age, as well as their perceptions regarding death. This is due to the understanding that there are innumerable questions that pervade old age, such as entering into another social role, as well as the real loss of the other - spouse, family, friends - as well as symbolic loss of self through work, of the body and its performance. It is understood that the study importance is given to the extent that space for speech and reflection is allowed to the elderly, in order to provide subsidies for health practices that are closer to their demands, as well as a more humanized look and care to the experience of old age. For that, an exploratory and descriptive research, based on the clinicalqualitative method was used. The subjects of the survey were searched for in a Family Health Strategy responsible for the eastern Region of Rio Grande do Sul state interior, which has a significant demand with elderly people, being the sample composed by the data saturation criteria. Data were collected through semi-structured interviews with open questions that with the consent of the participants were full transcript for analysis through content analysis. The research pledged to respect all ethical principles presented in the resolution 510/2016 that rules research with human beings. In this sense, the principles of autonomy, beneficence, efficiency, justice and equity will be respected, guaranteeing the rights and duties of the research participants, the scientific community and the State.